Pulmonary infiltrates in non-HIV immunocompromised patients: a diagnostic approach using non-invasive and bronchoscopic procedures. Issue 5 (1st May 2001) - Rañó, A; Agustí, C; Jimenez, P; Angrill, J; Benito, N; Danés, C; González, J; Rovira, M; Pumarola, T; Moreno, A; Torres, A
Abstract : BACKGROUND: The development of pulmonary infiltrates is a frequent life threatening complication in immunocompromised patients, requiring early diagnosis and specific treatment. In the present study non-invasive and bronchoscopic diagnostic techniques were applied in patients with different non-HIV immunocompromised conditions to determine the aetiology of the pulmonary infiltrates and to evaluate the impact of these methods on therapeutic decisions and outcome in this population. METHODS: The non-invasive diagnostic methods included serological tests, blood antigen detection, and blood, nasopharyngeal wash (NPW), sputum and tracheobronchial aspirate (TBAS) cultures. Bronchoscopic techniques included fibrobronchial aspirate (FBAS), protected specimen brush (PSB), and bronchoalveolar lavage (BAL). Two hundred consecutive episodes of pulmonary infiltrates were prospectively evaluated during a 30 month period in 52 solid organ transplant recipients, 53 haematopoietic stem cell transplant (HSCT) recipients, 68 patients with haematological malignancies, and 27 patients requiring chronic treatment with corticosteroids and/or immunosuppressive drugs. RESULTS: An aetiological diagnosis was obtained in 162 (81%) of the 200 patients. The aetiology of the pulmonary infiltrates was infectious in 125 (77%) and non-infectious in 37 (23%); 38 (19%) remained undiagnosed. The main infectious aetiologies were bacterial (48/125, 24%), fungal (33/125, 17%), and viral (20/125, 10%), and the most frequent pathogens were Aspergillus fumigatus (n=29), Staphylococcus aureus (n=17), and Pseudomonas aeruginosa (n=12). Among the non-infectious aetiologies, pulmonary oedema (16/37, 43%) and diffuse alveolar haemorrhage (10/37, 27%) were the most common causes. Non-invasive techniques led to the diagnosis of pulmonary infiltrates in 41% of the cases in which they were used; specifically, the diagnostic yield of blood cultures was 30/191 (16%); sputum cultures 27/88 (31%); NPW 9/50 (18%); and TBAS 35/55 (65%). Bronchoscopic techniques led to the diagnosis of pulmonary infiltrates in 59% of the cases in which they were used: FBAS 16/28 (57%), BAL 68/135 (51%), and PSB 30/125 (24%). The results obtained with the different techniques led to a change in antibiotic treatment in 93 cases (46%). Although changes in treatment did not have an impact on the overall mortality, patients with pulmonary infiltrates of an infectious aetiology in whom the change was made during the first 7 days had a better outcome (29% mortality) than those in whom treatment was changed later (71% mortality; p=0.001). CONCLUSIONS: Non-invasive and bronchoscopic procedures are useful techniques for the diagnosis of pulmonary infiltrates in immunocompromised patients. Bronchial aspirates (FBAS and TBAS) and BAL have the highest diagnostic yield and impact on therapeutic decisions.